Study of the Cumulative Dose Between Fractions of Lung Cancer Radiotherapy Based on CT and CBCT Image Deformable Registration Technology - Luo, Judong; Ma, Changdong; Yu, Shuang; Li, Zhenjiang; Ma, Changsheng (Frontiers in Physics, 2020)
Objective: To analyze the difference between planned dose and delivered dose by accumulating the dose based on CT and CBCT image deformable registration. Methods: The clinical data of 24 NSCLC (non-small cell lung cancer) patients receiving conformal radiotherapy or intensity-modulated radiotherapy (IMRT) were retrospectively analyzed. With the CBCT image of each week as the target image, we performed the deformation registration for CBCT images and planning CT images in RayStation. The delivered dose of CBCT images compared to the planning CT images was accumulated with the use of mapping relationships in registration. The differences in planned dose and accumulative dose of target and at-risk organs were compared. Results: The average planned and accumulative doses of GTV in 24 patients were 5832.45 ± 645.42 and 5750.65 ± 630.27 cGy, respectively (P < 0.05). The average planning target volume (PTV) in CT plans and accumulation plans reaching the prescription dose was 95.59 and 81.47% of the PTV (P > 0.05). At the stage of treatment, the volumes of the at-risk organs in CBCT images were not significantly different. There were no statistically significant differences in the probability of complications in the right lung, left lung, heart, total lung, or spinal cord (P > 0.05). Conclusion: With the dose deformable registration method, the dose caused by changes in the target anatomical structure of NSCLC patients was found. The dose to organs did not change much. However, in some patients, the received radiation in the target organ was less than the prescribed dose.